Review of the biology of plant psyllid (Cacopsylla pruni, Scopoli 1763), and its role in the spreading of European stone fruit yellows, ESFY-phytoplasma with Hungarian data - Bodnár, Dominika; Csüllög, Kitti; Tarcali, Gábor (Acta Agraria Debreceniensis, 2018)
The European stone fruit yellows (ESFY) phytoplasma disease caused by pathogen ’Ca. Phytoplasma prunorum’ induces serious damages in cherry, sour cherry, peach, and apricot orchards mostly in Europe. Its known vector is the plum psyllid (Cacopsylla pruni). Many articles report on the biology (morphology, taxonomy, life cycle etc.) and the method of transmission of the pathogen by the vector, and the possibilities of their control. This paper reviews our knowledge about the vector, and summarises the results of an inland research carried out in a northeastern Hungarian apricot orchards. Our goal was to show some important data for the farmers or anyone who is interested in this disease and its vector. And give some known method that we can protect our orchards against them to prevent the appearance of the disease. As the psyllid that became infected with the pathogen can hold its infectionous capacity during their lifetime, it is very important to have enough knowledge about their lifecycle, that we can determine the right time and method to control them. We also have to know how to identify them; therefore, this paper lists several important data which can be helpful. The most important keys of identification are their wing color, which dark borwn in the apex and brown is in the remaining part of the forewing. The length of the antennae is also an important factor, since other genuse’s species have longer antennae than twice the width of the head. C. pruni has as long antennae as twice the width of the head. They return to Prunus species in early spring and we have to protect our orhards in this period against them. We have to use preparations with a knock down effect on them to prevent the inoculation of the pathogen into the trees in our orchards.